Few-nucleon systems: status and results of investigations - Lyakhno, Yu.P. (Вопросы атомной науки и техники, 2013)
The model-independent calculation of the nuclei ground state and the states of scattering can be carried out with due regard for realistic NN and 3N forces between nucleons and also, with the use of exact methods of solving the many- body problem. The tensor part of NN interaction and 3NF's generate the lightest nuclei states with nonzero orbital momenta of nucleons. These states in the lightest nuclei are the manifestation of the properties of inter-nucleonic forces, and therefore, similar effects should be observed in all nuclei and also in all their excited states. In this paper primary attention is given to the investigation of the ⁴He nucleus.